Role of magnetic resonance imaging in evaluation of vault prolapse - Sharma, J. B.; Kamal, Mukesh; Pandey, Kavita; Hari, Smriti; Kumari, Rajesh; Aggarwal, Ashita; N., Nisha; Deoghare, Manasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Vault prolapse usually follows vaginal or abdominal hysterectomy and is usually associated with cystocele, rectocele and enterocele. Diagnosis is made clinically but magnetic resonance imaging can better detect enterocele than clinical finding. Methods: It was a prospective study over 3 years, so women presenting with vault prolapse, in which grading of vault prolapse was made clinically and by pelvic organ prolapse quantification (POPQ). Magnetic resonance imaging was performed for all cases to quantify prolapse and compare findings of MRI and POPQ with intraoperative findings of prolapse. Results: Mean age, parity, BMI were 58.4 years, 3.5, 22.71kg/m2 respectively. Most patients (75%) had vaginal hysterectomy while 25% had abdominal hysterectomy. Symptoms were pressure in lower abdomen and perineum (55%), bulge and feeling of mass descending in perineum (100%) and chronic constipation (60%). The type of prolapse was cystocele (100%), rectocele (100%), vault prolapse (100%) and enterocele (45%). MRI had agreement with intraoperative findings in 65% cases in cystocele, 45% cases in vault prolapse, 50% in rectocele but had much higher agreement of 88.8% for enterocele. While POPQ had higher agreement with intraoperative findings for cystocele (80%), vault prolapse (98%), rectocele (80%) but had poorer agreement for enterocele (66.6%). Conclusions: This study demonstrated that MRI was inferior in diagnosis of cystocele, rectocele and vault prolapse than POPQ but was superior in identification of enterocele than POPQ.